Small GTPase Ran and Ran-binding proteins - Nagai Masahiro; Yoneda Yoshihiro (Biomolecular Concepts, 2012)
Like many other small GTPases, Ran functions in eukaryotic cells as a molecular switch that cycles between GTP- and GDP-bound forms. Through the proper modulation of the GTP/GDP cycle, Ran functions with a number of Ran-binding proteins to control a broad array of fundamental cellular functions, including nucleocytoplasmic transport, mitotic spindle assembly, and nuclear envelope and nuclear pore complex formation. Recent studies have revealed that ‘Ran and Ran binding proteins’ are involved in a variety of functions involving cell fate determination, including cell death, cell proliferation, cell differentiation, and malignant transformation. In this review, we discuss recent progress on the functional link between the Ran system and tumorigenesis, which give clues to the molecular understanding of cancer biology.